The Strange Case of the Infarcted Myxoma. Issue 3 (22nd November 2015) - Pergolini, Amedeo; Zampi, Giordano; Tinti, Maria Denitza; Pontillo, Daniele; Di Paolo, Barbara; Buffa, Vitaliano; Pulignano, Giovanni; Pino, Paolo Giuseppe; Minardi, Giovanni; Musumeci, Francesco
Abstract : In the setting of an acute coronary syndrome, the differential diagnosis between a thrombus and a myxoma may be cumbersome. We describe the case of a patient presenting with an acute coronary syndrome associated with an aneurysmatic apical left ventricular myxoma. Mini‐Abstract: We describe the case of a patient presenting with an acute coronary syndrome associated with an aneurysmatic apical left ventricular myxoma.